Régimen subsidiado pensional: el caso en Medellín durante el periodo 1996-2008 (2014)
The object of this research article is to analyze the efficacy of universality principle in the pension subsidized regime for the case of Medellin during the years 1996- 2008. In one hand, it presents a theoretical reflection on universality as a socialsecurity principle; on the other hand, it presents the limitations that from a juridical point of view could be evidences in the pension subsidized regime. So from the analysis of data ad documentary sources, it was possible to conclude that pension subsidized regime is not an efficient tool for urban, rural independent workers, community mothers and disabled people could have access to a pension. In this way, it has been proposed as a challenge for social security policy, to increase the coverage of pension subsidize system in order to allow to large group of independent workers that wen they arrive to their retired age, has disability, or die can have an income allowing their subsistence and their families as well